FeCN-coated ZSM-5 composite material, PP diaphragm, lithium-sulfur battery and preparation process of lithium-sulfur battery
By using FeCN@ZSM-5 composite material to modify PP separators in lithium-sulfur batteries, the shortcomings of traditional PP separators and catalysts are solved, and more stable lithium-sulfur battery performance is achieved, especially the improvement of cycle performance and rate performance.
Patent Information
- Application Number
- CN202510674115.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-08-26
AI Technical Summary
In lithium-sulfur batteries, traditional PP separators have limited barrier capacity to lithium polysulfide, resulting in insufficient wettability of the electrolyte, affecting ion transmission efficiency, and insufficient activity and poor stability of existing catalysts, limiting battery performance.
The PP separator was modified by FeCN@ZSM-5 composite material, and FeCN@ZSM-5 was synthesized by hydrothermal method, and FeCN was introduced to increase the specific surface area and catalytic active sites, promote the conversion of polysulfides, and improve the diffusion of Li ions.
The cycling performance and rate performance of lithium sulfur batteries are improved, and the stable ion transport interface is provided in the PP separator through FeCN@ZSM-5 composite material, which promotes the conversion of polysulfides and the diffusion of Li ions, and improves the overall performance of the battery.
Smart Images

Figure CN120534987A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-sulfur battery materials, and specifically to a FeCN@ZSM-5 composite material, a PP diaphragm, a lithium-sulfur battery and a preparation process thereof. Background Art
[0002] In the current energy storage sector, which is constantly pursuing high efficiency and environmental friendliness, lithium-sulfur batteries, with their high theoretical energy density (up to 2600Wh / kg) and relatively low cost, are considered a highly promising next-generation energy storage technology and are attracting widespread attention. However, lithium-sulfur batteries face numerous challenges in practical application, limiting their commercialization.
[0003] Traditional battery separators also exhibit numerous deficiencies in lithium-sulfur battery systems. For example, while the chemical stability and mechanical properties of common polypropylene (PP) separators meet certain requirements, their barrier capacity for lithium polysulfides is limited, making them ineffective in suppressing the "shuttle effect." Furthermore, PP separators have poor lyophilization, resulting in insufficient electrolyte wettability, which affects ion transport efficiency and, in turn, reduces overall battery performance.
[0004] In terms of catalytic materials, some existing catalysts for promoting lithium polysulfide conversion reactions have problems such as insufficient activity, poor stability and high cost. Taking ZSM-5 molecular sieve as an example, when used alone, it is difficult to meet the actual demand for the catalytic conversion efficiency of lithium polysulfide, and the synthesis cost is high, which limits large-scale application. The advantages of ZSM-5 zeolite such as adjustable surface acidity, shape-selective catalysis, and good hydrothermal stability are ideal carriers for loading metal active centers. By loading transition metal elements (Co, Mn, V, Cr, Fe and Ti, etc.) with redox activity into zeolite to form hybrid catalysts, it is possible to obtain redox active centers that are separated from each other and highly dispersed, while having certain molecular sieve engineering, which can be used as a catalytic material with multifunctional cooperative coupling and good performance. However, ZSM-5 zeolite, which has excellent ion transport performance, is still challenged by its electrical conductivity due to its insulating properties. Summary of the Invention
[0005] The purpose of this application is to provide a FeCN@ZSM-5 composite material, a PP diaphragm, a lithium-sulfur battery and its preparation process. The application of FeCN@ZSM-5 in the PP diaphragm of the lithium-sulfur battery can provide a more stable ion transport interface, so that the device can obtain more stable cycle performance and rate performance.
[0006] In order to solve the above technical problems, the technical solutions adopted in this application are:
[0007] In a first aspect, the present application provides a preparation process of a FeCN@ZSM-5 composite material, comprising the following steps:
[0008] S1, adding ZSM-5 zeolite, Ppy and FeCl2 into water, stirring to form a uniform solution, then slowly adding H2O2, and continuing to stir to prepare FeCN@ZSM-5 precursor solution;
[0009] S2. Continue to add FeCl2 to the above FeCN@ZSM-5 precursor solution and stir. After standing, take the precipitated product and freeze-dry it to obtain FeCN@ZSM-5 precursor;
[0010] S3. Annealing the FeCN@ZSM-5 precursor to obtain a FeCN@ZSM-5 composite material.
[0011] In the second aspect, the present application provides a FeCN@ZSM-5 composite material prepared by the above preparation process, wherein the specific surface area of the composite material is 311.56m 2 g -1 , of which the external specific surface area is 95.96m 2 g -1 ; Total pore volume is 0.089cm 3 g -1 The specific surface area of micropores is 215.60m 2 g -1 .
[0012] In a third aspect, the present application provides a PP diaphragm formed by modifying a PP material with the above-mentioned FeCN@ZSM-5 composite material.
[0013] In a fourth aspect, the present application provides a lithium-sulfur battery comprising the above-mentioned PP separator.
[0014] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:
[0015] 1. This application synthesizes a FeCN@ZSM-5 composite material by a hydrothermal method. The results of mineralogical characterization show that the introduction of FeCN does not destroy the main structure of ZSM-5 zeolite. XPS results show that Fe-Nx compounds, Fe-C compounds, and Fe-O compounds are synthesized, and N mainly exists in the form of pyridinic nitrogen, Fe-Pyr N, pyrrolic nitrogen, graphitic nitrogen, and nitrogen oxide compounds. These compounds can improve the surface conductivity and provide more active sites for the redox chemical conversion process of polysulfides.
[0016] 2. BET specific surface area analysis results show that the introduction of FeCN increases the specific surface area of the material to 311.56m 2 g -1The introduction of functionalized active sites further improves the ion transport regulation ability of ZSM-5 zeolite and enhances its electrical conductivity.
[0017] 3. This application uses FeCN@ZSM-5 composite materials to modify PP separators. Experiments have shown that the introduction of FeCN can promote the conversion of polysulfides and reduce the interfacial charge transfer resistance, thereby promoting the diffusion of Li ions in the battery. The introduction of FeCN into the ZSM-5 zeolite structure enables the lithium-sulfur battery separator to catalytically regulate the polysulfide conversion reaction kinetics and improve interfacial conductivity to improve Li ion diffusion, thereby promoting lithium-sulfur batteries to achieve superior overall battery performance.
[0018] In summary, the FeCN@ZSM-5 composite material synthesized using Ppy as a carbon-nitrogen source and FeCl2 as a transition metal source can provide more catalytic active sites for polysulfide conversion in lithium-sulfur batteries, form an interface for rapid lithium ion diffusion, and at the same time improve the poor electronic conductivity of ZSM-5. Applying FeCN@ZSM-5 to the PP separator of lithium-sulfur batteries can provide a more stable ion transport interface, resulting in more stable cycle performance and rate performance of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without creative work.
[0020] Figure 1 Schematic diagram of the preparation process of FeCN@ZSM-5 material in Example 1 of this application;
[0021] Figure 2 This is the XRD pattern of the FeCN@ZSM-5 material in Example 2 of the present application;
[0022] Figure 3 This is the SEM surface morphology of FeCN@ZSM-5 in Example 3 of this application;
[0023] Figure 4 This is a partial element distribution diagram of FeCN@ZSM-5Mapping in Example 3 of this application;
[0024] Figure 5 This is the full XPS spectrum of FeCN@ZSM-5 in Example 4 of this application;
[0025] Figure 6This is the Fe 2p binding energy spectrum of FeCN@ZSM-5 in Example 4 of the present application;
[0026] Figure 7 This is the C1s binding energy spectrum of FeCN@ZSM-5 in Example 4 of the present application;
[0027] Figure 8 This is the N1s binding energy spectrum of FeCN@ZSM-5 in Example 4 of the present application;
[0028] Figure 9 This is the adsorption-desorption isotherm curve of 5FeCN@ZSM-5N2 in Example 5 of the present application;
[0029] Figure 10 This is the pore size distribution curve of FeCN@ZSM-5 in Example 5 of this application;
[0030] Figure 11 CV curves of ZSM-5 and FeCN@ZSM-5 symmetric cells of Example 6 of the present application;
[0031] Figure 12 This is the EIS spectrum of the ZSM-5 and FeCN@ZSM-5 symmetric cells in Example 6 of the present application;
[0032] Figure 13 This is the time-voltage cycling curve of the FeCN@ZSM-5 lithium symmetric battery in Example 7 of the present application;
[0033] Figure 14 This is a partial enlarged view of the time-voltage cycle curve of the FeCN@ZSM-5 lithium symmetric battery in Example 7 of the present application;
[0034] Figure 15 This is the voltage hysteresis curve of the FeCN@ZSM-5 lithium symmetric battery test in Example 7 of the present application;
[0035] Figure 16 CV curves of ZSM-5 / PP and FeCN@ZSM-5 / PP Li-S batteries of Example 8 of the present application, wherein (a) represents the CV curve of ZSM-5 / PP at different scan rates, (b) represents the CV curve of FeCN@ZSM-5 / PP at different scan rates, (c) represents a linear comparison graph of the current density of ZSM-5 / PP and the scan rate, and (d) represents a linear comparison graph of the current density of FeCN@ / PP and the scan rate;
[0036] Figure 17 The cycling performance curves of ZSM-5 / PP and FeCN@ZSM-5 / PP Li-S batteries at 1C are shown in Example 8 of the present application.
[0037] Figure 18The charge-discharge cycle curves of ZSM-5 / PP and FeCN@ZSM-5 / PP Li-S batteries of Example 8 of the present application at C, where (a) is the ZSM-5 / PPLi-S battery and (b) is the FeCN@ZSM-5 / PP Li-S battery;
[0038] Figure 19 This is the rate performance curve of ZSM-5 / PP and FeCN@ZSM-5 / PP Li-S batteries in Example 8 of this application. DETAILED DESCRIPTION
[0039] To make the purpose, technical solutions and advantages of the examples of the present application clearer, the technical solutions in the examples of the present application will be described clearly and completely below. Where specific conditions are not specified in the examples, conventional conditions or conditions recommended by the manufacturer are used. Where the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0040] It should be noted that, in the absence of conflict, the embodiments and features of the embodiments in this application can be combined with each other. The present application will be described in detail below with reference to specific embodiments.
[0041] A preparation process of a FeCN@ZSM-5 composite material comprises the following steps:
[0042] S1. Add ZSM-5 zeolite, pyrrole (Ppy) and FeCl2 into water, stir magnetically to form a uniform solution, then slowly add H2O2 and continue stirring in the dark to prepare FeCN@ZSM-5 precursor solution;
[0043] S2. Continue to add FeCl2 to the above FeCN@ZSM-5 precursor solution and stir. After standing, take the precipitated product and freeze-dry it to obtain FeCN@ZSM-5 precursor;
[0044] S3. Annealing the FeCN@ZSM-5 precursor to obtain a FeCN@ZSM-5 composite material.
[0045] In some embodiments of the present application, in the above step S1, the addition ratio of ZSM-5 zeolite, Ppy and FeCl2 is 0.5g:2mL:0.2g, and the addition amount of H2O2 is 10%-15%vol, preferably 10%vol.
[0046] In some embodiments of the present application, after adding H2O2 in the above step S1, the mixture is stirred for 24 hours in a dark environment.
[0047] In some embodiments of the present application, the amount of FeCl2 used in the above-mentioned step S2 is 30-40mM, preferably 40mM.
[0048] In some embodiments of the present application, the stirring time in the above step S2 is 3 hours, the standing time is 24 hours, and the freeze-drying temperature is -50°C, and the time is 48 hours.
[0049] In some embodiments of the present application, the annealing treatment in the above step S3 is specifically annealing at 800° C. for 5 hours in an argon atmosphere.
[0050] A FeCN@ZSM-5 composite material prepared by the above preparation process has a specific surface area of 311.56m 2 g -1 , of which the external specific surface area is 95.96m 2 g -1 ; Total pore volume is 0.089cm 3 g -1 The specific surface area of micropores is 215.60m 2 g -1 The average pore size is 2.09nm, and the pore size is mainly distributed between 3-4nm.
[0051] A PP diaphragm is prepared by modifying a PP material using the FeCN@ZSM-5 composite material. The specific preparation method includes the following steps:
[0052] A1. Disperse the above-mentioned FeCN@ZSM-5 composite material powder, super P, and polyvinylidene fluoride powder in N-methyl-2-pyrrolidone solvent and stir to obtain a uniform composite slurry;
[0053] A2. Using a pure PP membrane as a substrate, the composite slurry was coated on the pure PP membrane, and the solvent was removed by drying to obtain a FeCN@ZSM-5 / PP membrane;
[0054] Furthermore, in the above step A1, the mass ratio of FeCN@ZSM-5 composite material powder, super P, and polyvinylidene fluoride powder is 8:1:1, and the stirring time is 24 hours.
[0055] Furthermore, in the above step A2, the composite slurry is coated on the PP diaphragm by vacuum filtration; and the drying is performed by vacuum drying at a temperature of 60° C. for 12 h.
[0056] A lithium-sulfur battery comprises the modified PP separator.
[0057] The features and performance of the present application are further described in detail below with reference to the embodiments.
[0058] Example 1
[0059] In this embodiment, a FeCN@ZSM-5 composite material is prepared, and the steps are as follows:
[0060] S1. Add 0.5 g ZSM-5 zeolite, 2 mL pyrrole (Ppy), and 0.2 g FeCl2 to 88 mL water, stir magnetically to form a homogeneous solution, then slowly add 10 mL H2O2, continue to shield from light and stir for 24 h to prepare the FeCN@ZSM-5 precursor solution;
[0061] S2. Add 0.5 g of FeCl2 to the above FeCN@ZSM-5 precursor solution and stir for 3 h. After standing for 24 h, take the precipitated product and freeze-dry it to obtain the FeCN@ZSM-5 precursor;
[0062] S3. The FeCN@ZSM-5 precursor is placed in a tube furnace and annealed at 800°C for 5 h to obtain a FeCN@ZSM-5 composite material.
[0063] The schematic diagram of the preparation process is shown in Figure 1 shown.
[0064] Example 2
[0065] In this example, the phase composition of the FeCN@ZSM-5 composite material prepared in Example 1 was analyzed, and its XRD pattern was as follows: Figure 2 As shown, from Figure 2 It can be seen that the characteristic peaks of the crystal planes (100), (101), (111), and (201) of Fe3N (PDF#49-1663) appear at 21.8°, 30.0°, 43.7°, and 49.4°, and the characteristic peaks of the crystal planes (020), (031), (131), and (122) of Fe3C (PDF#35-0772) appear at 26.4°, 45.0°, 48.6°, and 51.8°. At the same time, strong diffraction peaks of ZSM-5 zeolite also appear at 7.9°, 8.8°, 23.1°, 23.8°, and 24.3°, which indicates that the FeCN@ZSM-5 material was successfully synthesized and the main crystal structure of ZSM-5 zeolite did not change.
[0066] Example 3
[0067] In this example, the morphology of the FeCN@ZSM-5 composite material prepared in Example 1 was analyzed.
[0068] The morphology of FeCN@ZSM-5 composite material observed by scanning electron microscope is shown in Figure 2. Figure 3 As shown. Figure 3 It can be seen that there are some petals on the surface of ZSM-5 zeolite, which is similar to the microscopic morphology of the FeCN composite material synthesized separately in the early stage. In addition, ZSM-5 zeolite still presents coffin-shaped crystals with clear outlines, which is consistent with the XRD phase structure characterization.
[0069] DES was used to analyze the composition elements of FeCN@ZSM-5 composite materials. The distribution of some elements in FeCN@ZSM-5Mapping is as follows: Figure 4 As shown in the figure, it is clearly visible that the Fe, C, and N elements are evenly distributed on the surface of the ZSM-5 material, with the outline of the ZSM-5 crystal as the boundary, further confirming that Fe, C, and N have successfully incorporated into the framework of the ZSM-5 zeolite structure. The successful doping of FeCN is expected to improve the conductivity of the ZSM-5 zeolite surface.
[0070] Example 4
[0071] In this example, the chemical composition of the FeCN@ZSM-5 composite material prepared in Example 1 was analyzed.
[0072] The chemical structure of FeCN@ZSM-5 surface was analyzed by X-ray photoelectron spectroscopy (XPS). The full XPS spectrum of FeCN@ZSM-5 is shown in Figure 2. Figure 5 As shown in Figure 2, the material is composed of Si, Al, O, Fe, C, and N. The binding energy spectrum of Fe 2p ( Figure 6 ) is composed of Fe 2p3 / 2 and Fe 2p1 / 2, which belong to Fe-Nx compounds, Fe-C compounds, and Fe-O compounds, respectively, which is consistent with the XRD characterization results, proving that FeCN@ZSM-5 is successfully synthesized.
[0073] From the C1 binding energy spectrum ( Figure 7 ) It can be seen that the characteristic peaks of C=O, CN, and CC / C=C appear at 288.8, 286.3, and 284.7 eV. The N1s binding energy spectrum of FeCN@ZSM-5 ( Figure 8 ) Five characteristic peaks of nitrogen bonds appeared at 397.3, 397.9, 398.5, 399.3, and 400.3 eV, corresponding to pyridinic nitrogen, Fe-Pyr N, pyrrolic nitrogen, graphitic nitrogen, and nitrogen oxide compounds, respectively. Among these nitrogen compounds, the formation of pyridinic nitrogen and Fe-Pyr N bonds can catalyze the conversion of polysulfides in lithium-sulfur batteries, while the formation of graphitic nitrogen bonds helps improve the conductivity of the material. This indicates that the hybridization of FeCN in ZSM-5 zeolite can form graphitic nitrogen bonds on the zeolite surface, thereby improving the conductive properties. In addition, the presence of catalytically active pyridinic nitrogen and Fe-Pyr N bonds will provide more catalytically active sites on the ZSM-5 surface.
[0074] Example 5
[0075] In this example, the specific surface area and pore size of the FeCN@ZSM-5 composite material prepared in Example 1 were analyzed.
[0076] The BET test analysis data of FeCN@ZSM-5 is as follows Figure 9 、 Figure 10 As shown in Table 1, it can be seen that the specific surface area of the material increases slightly after FeCN loading (311.56m 2 g -1 ), of which the external specific surface area (95.96m 2 g -1 ) increased significantly, which was due to the petal-like growth of FeCN on the ZSM-5 surface, which was consistent with the SEM characterization results. However, the total pore volume (0.089 cm 3 g -1 ), micropore specific surface area (215.60m 2 g -1 ) and the average pore size (2.09 nm) decreased, which may be due to the loading of FeCN on the pore surface. Figure 10 The pore size distribution curve of FeCN@ZSM-5 shows that its pore size is mainly distributed between 3-4 nm.
[0077] Table 1 Specific surface area and pore structure parameters of FeCN@ZSM-5
[0078]
[0079] Example 6
[0080] This example studies the catalytic conversion of polysulfides by FeCN@ZSM-5.
[0081] In order to demonstrate the promoting effect of FeCN-doped ZSM-5 on the conversion of polysulfides, the conversion of polysulfides on the surfaces of ZSM-5 and FeCN@ZSM-5 was studied using a symmetric cell system. 0.1M Li2S6 electrolyte was used as the target polysulfide, and CV and EIS tests were performed.
[0082] The CV curves of ZSM-5 symmetric battery and FeCN@ZSM-5 symmetric battery are shown in Figure 2. Figure 11As shown, a reversible redox reaction occurs in the symmetric cell. The FeCN@ZSM-5 symmetric cell shows two obvious reduction peaks during the reduction process. The reduction peak of Li2S6 reduced to Li2S2 appears at -0.055V, while the reduction peak of Li2S2 reduced to Li2S appears at -0.271V. Similarly, the FeCN@ZSM-5 symmetric cell also shows two peaks during the oxidation process, at 0.052V and 0.267V respectively. The oxidation peak at 0.052V corresponds to the process of Li2S oxidation to form polysulfides, while the oxidation peak at 0.267V corresponds to the process of polysulfide oxidation to elemental S8. In comparison, the ZSM-5 symmetric cell also shows two pairs of redox peaks, but the peak current is smaller and the electrochemical polarization voltage is higher (reduction peaks correspond to -0.313V and -0.059V, oxidation peaks correspond to 0.058V and 0.267V). These results indicate that the introduction of FeCN catalytic active sites promotes the conversion reaction between soluble polysulfides and solid Li2S2 / Li2S.
[0083] The electrochemical impedance spectroscopy of ZSM-5 symmetric battery and FeCN@ZSM-5 symmetric battery ( Figure 12 ) analysis shows that compared with the ZSM-5 symmetric battery, the electrochemical impedance spectrum of the FeCN@ZSM-5 symmetric battery has an arc with a significantly smaller radius at high frequencies, which further proves that polysulfides can undergo rapid chemical conversion on the FeCN@ZSM-5 surface.
[0084] Example 7
[0085] This example studies the mechanism of action of FeCN@ZSM-5 on Li ions.
[0086] This example further explores the effect of the modified diaphragm on the negative electrode lithium through Li||Li symmetric battery testing. The preparation method of FeCN@ZSM-5 / PP diaphragm is as follows:
[0087] (1) FeCN@ZSM-5 powder, super P, and polyvinylidene fluoride (PVDF) powder were dispersed in N-methyl-2-pyrrolidone (NMP) at a mass ratio of 8:1:1 and stirred for 24 h to obtain a uniform composite slurry;
[0088] (2) Using Celgard PP membrane as the substrate, the slurry is coated by vacuum filtration to ensure good bonding with the PP membrane, avoiding coating problems caused by insufficient or excessive infiltration, and achieving the best uniform film formation effect;
[0089] (3) The slurry-coated membrane was then placed in a vacuum drying oven at 60°C for 12 h to ensure the removal of the NMP solvent;
[0090] (4) Finally, a FeCN@ZSM-5 modified PP membrane (FeCN@ZSM-5 / PP membrane) with an appropriate FeCN@ZSM-5 / C coating thickness was obtained, and FeCN@ZSM-5 / C formed a black uniform and dense film on the surface of the PP membrane.
[0091] The Li symmetric battery assembled by FeCN@ZSM-5 / PP separator was charged and discharged at a current of 2 mA to test its voltage change over time. The battery electrolyte used was Li-S electrolyte (1M LiTFSI in DOL:DME=1:1Vol% with 2.0%LiNO3). Figure 13 、 Figure 14 is the time-voltage cycle curve (where Figure 14 The middle ab picture is Figure 13 (A magnified portion of the image shows that the FeCN@ZSM-5 separator exhibits excellent stability in lithium symmetric batteries, sustaining stable cycling for over 1200 hours with a relatively stable overpotential. Observing the voltage-time curves around 200 and 1240 hours reveals a remarkably stable overpotential, remaining around ±0.012V.
[0092] By analyzing the voltage hysteresis curve of the battery ( Figure 15 ) found that the median voltage over time was approximately 12 mV, with a higher voltage initially due to battery activation. The excellent cycling stability and stable charge-discharge capacity of the lithium symmetry of the FeCN@ZSM-5 / PP separator indicate that FeCN@ZSM-5 can enhance the flux of lithium ions from the negative electrode to the positive electrode, effectively promoting the conversion of polysulfides in the sulfur positive electrode while suppressing the growth of lithium dendrites in the negative electrode.
[0093] Example 8
[0094] This example studies the effect of FeCN@ZSM-5 modified diaphragm on the electrochemical performance of Li-S batteries.
[0095] To further analyze the synergistic regulation of anionic polysulfides and cationic Li ions at the separator interface by FeCN@ZSM-5, a PP separator modified with FeCN@ZSM-5 was used in lithium-sulfur (Li-S) batteries by characterizing battery CV, EIS, cycling, and rate performance. The effects of the FeCN@ZSM-5 / PP separator on the conversion of polysulfides, the transport mechanism of Li ions, and the battery cycling stability and rate charge-discharge performance were systematically studied.
[0096] The following is the CV test analysis of Li-S battery based on FeCN@ZSM-5 / PP separator:
[0097] The CV test analysis results of ZSM-5 / PP and FeCN@ZSM-5 / PP Li-S batteries at scan rates of 0.1mV / s, 0.2mV / s, 0.3mV / s, and 0.4mV / s are shown in Figure 2. Figure 16 As shown ((a) CV curves of ZSM-5 / PP at different scan rates, (b) CV curves of FeCN@ZSM-5 / PP at different scan rates, (c) linear comparison of current density of ZSM-5 / PP and scan rate, (d) linear comparison of current density of FeCN@ / PP and scan rate). As can be seen from the figures, both cells exhibit two pairs of distinct redox peaks. The high-voltage reduction peak at around 2.3V corresponds to the reduction of elemental sulfur to long-chain polysulfides (Li2Sn, 4≤n≤8), and the reduction peak near 2V corresponds to the further reduction of polysulfides to short-chain Li2S2 / Li2S. In addition, the oxidation peak near 2.4V represents the process of converting insoluble lithium sulfide to long-chain lithium polysulfide and finally to elemental sulfur. The FeCN@ZSM-5 / PP cell exhibits a higher peak current in the CV curve and a smaller range voltage at different scan rates, indicating that FeCN@ZSM-5 has more sufficient redox kinetics for polysulfides.
[0098] According to the Randles-Sevcik equation, the linear relationship between the peak current intensity of the positive and negative electrodes and the square root of the scan rate is as follows: Figure 17 The results show that the FeCN@ZSM-5 / PP battery can be cycled quite stably for 1000 cycles. Its initial discharge capacity is 1164.2 mA h g-1, and after 1000 cycles, it still has 371.5 mA h g-1, with a capacity loss rate of only 0.065% per cycle. In contrast, the initial discharge capacity of the ZSM-5 / PP battery is 1024.4 mA h g-1, but after 1000 cycles, it only has 260.2 mA h g-1, with a capacity loss rate of 0.071% per cycle. This shows that the FeCN-doped ZSM-5 zeolite can effectively promote the conversion of polysulfides and reduce the diffusion barrier of lithium ions.
[0099] Analysis of the charge-discharge cycle curves of ZSM-5 / PP and FeCN@ZSM-5 / PP Li-S batteries under C ( Figure 18 ) found that two discharge plateaus appeared near 2.3V and 2V, corresponding to the transformation of long-chain polysulfides and short-chain polysulfides, respectively. In comparison, the discharge plateau of the FeCN@ZSM-5 / PP Li-S battery was more obvious, and the platform for the transformation of short-chain polysulfides was very stable, indicating that the sulfur utilization rate was more efficient throughout the discharge process.
[0100] The cycle charge and discharge performance of ZSM-5 / PP and FeCN@ZSM-5 / PP Li-S batteries at different rates were further verified by rate performance test ( Figure 19 From the analysis of the battery rate charge and discharge cycle number, specific capacity and Coulomb efficiency curve, it is known that the first cycle discharge specific capacity of the ZSM-5 / PP Li-S battery at 0.1C, 0.2C, 0.5C, 1C, 2C and 3C is 1417.9mAh g -1 、866.1mA hg -1 , 741.3mAh g -1 、663.7mAh g -1 、550.2mAh g -1 、477.7mAh g -1 The first cycle discharge capacity of ZSM-5 / PP Li-S battery at 0.1C, 0.2C, 0.5C, 1C, 2C, and 3C is 1393.3 mAh g -1 、876.2mAh g -1 , 700.8mAh g -1 、591.8mAh g -1 、504.8mA hg -1 , 420.1mAhg -1 Table 2 shows the capacity loss statistics of ZSM-5 / PP and FeCN@ZSM-5 / PP Li-S batteries at different rates. It can be seen that the charge and discharge cycle stability of FeCN@ZSM-5 / PP Li-S battery is better at high rates, which provides the possibility for fast charging of the battery.
[0101] Table 2 Statistics of capacity loss of ZSM-5 / PP and FeCN@ZSM-5 / PP Li-S batteries at different rates
[0102]
[0103]
[0104] Finally, the electrochemical performance of lithium-sulfur batteries using the ZSM-5 / PP, Li-ZSM-5 / PP, and FeCN@ZSM-5 / PP membranes studied in this application was compared with the electrochemical performance of previously reported membranes, as shown in Table 3. The comparison found that the battery studied in the paper had higher charge and discharge performance at high rates, and showed longer cycle life and smaller capacity decay rate in long-term cycle tests. This indicates that ZSM-5-based zeolite mineral materials can improve the device's charge and discharge cycle performance and high-rate charge and discharge performance by improving the transport performance of polysulfide anions and Li ions in the modification of lithium-sulfur battery membranes. In addition, the simple preparation process of ZSM-5 / PP, Li-ZSM-5 / PP, and FeCN@ZSM-5 / PP membranes will be more suitable for practical applications.
[0105] Table 3 Comparative statistics of lithium-sulfur battery separator modification in this application and previously reported work
[0106]
[0107]
[0108] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
Claims
1. A preparation process of FeCN@ZSM-5 composite material, characterized in that: The following steps are involved: S1. Add ZSM-5 zeolite, Ppy, and FeCl2 into deionized water, stir to form a uniform solution, then slowly add H2O2 and continue stirring to prepare a FeCN@ZSM-5 precursor solution; S2. Continue to add FeCl2 to the above FeCN@ZSM-5 precursor solution and stir. After standing, take the precipitated product and freeze-dry it to obtain FeCN@ZSM-5 precursor; S3. Annealing the FeCN@ZSM-5 precursor to obtain a FeCN@ZSM-5 composite material.
2. The preparation process of a FeCN@ZSM-5 composite material according to claim 1, characterized in that: In the step S1, the addition ratio of ZSM-5 zeolite, Ppy and FeCl2 is 0.5g:2mL:0.2g, and the addition amount of H2O2 is 10%-15%vol.
3. The preparation process of a FeCN@ZSM-5 composite material according to claim 1, characterized in that: After adding H2O2 in step S1, the mixture was stirred for 24 hours in a dark environment.
4. The preparation process of a FeCN@ZSM-5 composite material according to claim 1, characterized in that: The amount of FeCl2 used in the S2 step is 30-40mM.
5. The preparation process of a FeCN@ZSM-5 composite material according to claim 1, characterized in that: In the step S2, the stirring time is 3 hours and the standing time is 24 hours; the freeze-drying temperature is -50°C and the time is 48 hours.
6. The preparation process of a FeCN@ZSM-5 composite material according to claim 1, characterized in that: The annealing treatment in step S3 is specifically annealing at 800° C. for 5 hours in an argon atmosphere.
7. A FeCN@ZSM-5 composite material prepared by the preparation process according to any one of claims 1 to 6, characterized in that: The specific surface area of the composite material is 311.56 m 2 g -1 , of which the external specific surface area is 95.96m 2 g -1 ; Total pore volume is 0.089cm 3 g -1 The specific surface area of micropores is 215.60m 2 g -1 .
8. A PP diaphragm, characterized in that: The PP material is modified by using the FeCN@ZSM-5 composite material described in claim 7.
9. A PP diaphragm according to claim 8, characterized in that: The preparation method of the PP diaphragm comprises the following steps: A1. Disperse the above-mentioned FeCN@ZSM-5 composite material powder, super P, and polyvinylidene fluoride powder in N-methyl-2-pyrrolidone solvent and stir to obtain a uniform composite slurry; A2. Using pure PP membrane as the substrate, the composite slurry was coated on the pure PP membrane, and the solvent was removed by drying to obtain the modified FeCN@ZSM-5 / PP membrane.
10. A lithium-sulfur battery, characterized in that: Including the PP diaphragm according to claim 8 or 9.